FORMATION AND EVOLUTION OF THE DANUBE DELTA (PANGEEA, 2025)
The Danube Delta is the newest territory of Romania. Its formation took place in several stages, from Paleozoic to Pliocene. During this time, six geological cycles were highlighted. The most important stage in the formation of the Danube Delta is the Deltaic stage because no orogenic movements have taken place, erosion due to the winds and precipitation has taken place and the main cracks have formed. Around these beams the floods brought by the Danube river accumulated, which led to the formation of the current delta.
Keywords: Danube Delta; geology; cycles; stages; levees; sediments; clogging